(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article discusses the issues of improving the electronic information system for the effective organization of the educational process in medical universities, the use of innovative technologies in medical education, the introduction, application, assessment and organization of medical education based on effective innovative technologies.